Proceso de ambientación escolar en el desarrollo emocional, de los niños de 4 a 5 años en el centro de Educación Inicial Pekelandia, ciudad de Riobamba - Gavilanes Robles, Rosario Estefania (2023)
The research work entitled “Process of School Setting in the Emotional Development of Children Aged 4 to 5 years” the objective of this research was to analyze the impact of the process of school setting in the emotional development of children aged 4 to 5 years at the Pekelandia Initial Education Center, located in the city of Riobamba, province of Chimborazo. The study was carried out through field research of a basic and bibliographic nature. Using a descriptive and documentary approach methodology, the study population was made up of 26 children who were enrolled in initial level 2 at the CEI Pekelandia. To carry out this research, the observation technique was used. In this sense, a structured observation sheet was designed that consisted of 9 indicators. These indicators were assessed using a binary response scale, I.e., “Yes” or “No”. The analysis of the information obtained revealed the existence of direct factors that affect the behavior of children, which does not favor adequate development in the school environment process, especially from the social, emotional, and psychological perspectives of the children. These findings benefit preschool teachers, who will consider the aspects mentioned as problematic to improve the setting process and provide a more conducive environment for the comprehensive development of children.